Blockchain Technology in Accounting: A Paradigm Shift in Transparency and Efficiency in the UK - Chen, Junwei (Journal of Ecohumanism, 2024)
Background: Traditional accounting processes face challenges like data manipulation, fraud, and inefficiencies in the processes. Blockchain in accounting provides full transparency, where auditors, accountants, and clients can have access to identical ledgers for verifying the information. Objectives: To evaluate the impact of Blockchain technology on transparency and efficiency in the accounting profession in the United Kingdom. Methodology: This research follows a quantitative research method. The survey method has been used for collecting data from accountants, auditors, CFOs, financial analysts, and others. In this study, questionnaires have been sent to the accounting professionals from the big four accounting firms in London, United Kingdom. The raw data has been gathered from a total of 156 people participants from the accounting firms. A questionnaire has been used in the study, where various independent and dependent variables are identified. Findings/conclusions: The results show that Blockchain security, cost, adoption, and implementation have a positive and significant influence on transparency. On the other hand, Blockchain security, cost, adoption and implementation, compliance, and performance have a positive and significant influence on efficiency. Lastly, it is identified that Blockchain efficiency and transparency have a positive and significant influence on stakeholder trust among accounting firms in London, UK. Policy Recommendations: The first policy recommendation is promoting the adoption of Blockchain among accounting firms. Tax incentives can be provided to accounting organizations that are heavily investing in Blockchain technology. Besides, regulatory frameworks, development programs, and comprehensive guidelines can help in guiding the adoption of Blockchain technology among accounting firms.